2009
DOI: 10.1016/j.neurobiolaging.2008.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion and oxygenation differences in Alzheimer's disease risk

Abstract: Functional MRI has demonstrated differences in response to memory performance based on risk for Alzheimer's disease (AD). The current study compared blood oxygen level dependent (BOLD) functional MRI response with arterial spin labeling (ASL) perfusion response during an associative encoding task and resting perfusion signal in different risk groups for AD. Thirteen individuals with a positive family history of AD and at least one copy of the apolipoprotien E ε4 (APOE4) gene (high risk) were compared to ten in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 70 publications
(98 reference statements)
7
138
3
Order By: Relevance
“…19 Conjunction analysis showed that the overlap between the 2 modalities in these areas was statistically significant. Contrary to several reports of hyperperfusion in the hippocampus for patients with prodromal AD, [27][28][29] we did not find any areas with mismatched CBF and CMRGlc, suggesting that the elevated hippocampal CBF was likely a compensatory mechanism only present in early disease stages. Complementary to the voxel-wise comparison, the ROI results showed significantly lower rCBF and rCMRGlc in the angular and posterior cingulate areas of the patients, while motor, thalamus, and basal ganglia regions were unaffected.…”
Section: Resultscontrasting
confidence: 99%
“…19 Conjunction analysis showed that the overlap between the 2 modalities in these areas was statistically significant. Contrary to several reports of hyperperfusion in the hippocampus for patients with prodromal AD, [27][28][29] we did not find any areas with mismatched CBF and CMRGlc, suggesting that the elevated hippocampal CBF was likely a compensatory mechanism only present in early disease stages. Complementary to the voxel-wise comparison, the ROI results showed significantly lower rCBF and rCMRGlc in the angular and posterior cingulate areas of the patients, while motor, thalamus, and basal ganglia regions were unaffected.…”
Section: Resultscontrasting
confidence: 99%
“…A number of studies (33,34) have shown that increases or decreases in BOLD response between young and old individuals could easily arise as artifacts of basal state factors such as metabolic rate and neurovascular coupling. With this caveat in mind, testing a main effect of group would have been difficult to interpret (this difference was sig- Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, reduced left entorhinal cortex thickness was reported in a large study of child and adolescent 4-carriers relative to noncarriers (19), although this difference was influenced by larger volumes in 2-carriers. Older 4-carriers have also been reported to have increased resting cerebral blood flow relative to noncarriers (40). Sample size or age may have contributed to the lack of significant difference in morphological features or resting perfusion between 4-carriers and noncarriers.…”
Section: Discussionmentioning
confidence: 99%